2017
DOI: 10.1002/acn3.425
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing markers in spinal and bulbar muscular atrophy

Abstract: ObjectiveWe examined the characteristics of dysphagia in spinal and bulbar muscular atrophy, a hereditary neuromuscular disease causing weakness of limb, facial, and oropharyngeal muscles via a videofluoroscopic swallowing study, and investigated the plausibility of using these outcome measures for quantitative analysis.MethodsA videofluoroscopic swallowing study was performed on 111 consecutive patients with genetically confirmed spinal and bulbar muscular atrophy and 53 age‐ and sex‐matched healthy controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Findings from fluoroscopic investigations examining the physiological correlates for these symptoms support these clinical reports of reduced severity of deficits. Videofluoroscopic results indicate patients with SMA Types II–IV typically have much lower rates of bolus airway entry ( Banno et al, 2017 ; Cha et al, 2010 ; Hashizume et al, 2017 ; van den Engel-Hoek et al, 2009 ). Though a case report of a 25-year-old patient with SMA Type II revealed impaired laryngeal closure resulting in aspiration ( Cha et al, 2010 ), other larger investigations have indicated none of their participants exhibited aspiration and 0%–26% of patients exhibited penetration ( Banno et al, 2017 ; van den Engel-Hoek et al, 2009 ).…”
Section: Review Of Pertinent Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Findings from fluoroscopic investigations examining the physiological correlates for these symptoms support these clinical reports of reduced severity of deficits. Videofluoroscopic results indicate patients with SMA Types II–IV typically have much lower rates of bolus airway entry ( Banno et al, 2017 ; Cha et al, 2010 ; Hashizume et al, 2017 ; van den Engel-Hoek et al, 2009 ). Though a case report of a 25-year-old patient with SMA Type II revealed impaired laryngeal closure resulting in aspiration ( Cha et al, 2010 ), other larger investigations have indicated none of their participants exhibited aspiration and 0%–26% of patients exhibited penetration ( Banno et al, 2017 ; van den Engel-Hoek et al, 2009 ).…”
Section: Review Of Pertinent Literaturementioning
confidence: 99%
“…Videofluoroscopic results indicate patients with SMA Types II–IV typically have much lower rates of bolus airway entry ( Banno et al, 2017 ; Cha et al, 2010 ; Hashizume et al, 2017 ; van den Engel-Hoek et al, 2009 ). Though a case report of a 25-year-old patient with SMA Type II revealed impaired laryngeal closure resulting in aspiration ( Cha et al, 2010 ), other larger investigations have indicated none of their participants exhibited aspiration and 0%–26% of patients exhibited penetration ( Banno et al, 2017 ; van den Engel-Hoek et al, 2009 ). Interpretation of these findings requires careful consideration to natural variants in deficits by SMA type, as well as findings from healthy, nondysphagic adults, which indicate 2% demonstrate aspiration and 9% demonstrate penetration on a videofluoroscopic swallow study ( Garand et al, 2019 ).…”
Section: Review Of Pertinent Literaturementioning
confidence: 99%
“…Patients with spinal and bulbar muscular atrophy (SBMA), another type of motor neuron disease, also develop dysphagia in both oral and pharyngeal phases. In patients with SBMA, pharyngeal phase abnormalities are more frequently observed than oral phase abnormalities (Banno et al., ). Patients with Parkinson’s disease, one of the most common neurodegenerative diseases, also frequently develop dysphagia.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis of dysphagia in PD may prevent hospitalization, disability, deaths, and global burden 13 for which periodical evaluation of oromotor function is required. Clinically early assessment is crucial for patient prognosis 14 and available gold standard tools videofluoroscopy (VFS) or Flexible endoscopic evaluations of swallowing (FEES) are still with constraints 2,15,16,17,18,19 . If such diagnosis is complemented with non-invasive, patient and environment friendly objective investigation, it will facilitate early identification, optimal intervention with better prognosis and reducing the morbidity.…”
Section: Introductionmentioning
confidence: 99%